ANALISIS EFEKTIFITAS PEMBELAJARAN DARING PADA MATA PELAJARAN PKn DI KELAS XI SMAN 1 TUALANG KABUPATEN SIAK - Rahmi Rahmi; Sri Erlinda; Supentri Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research was conducted to determine the effectiveness of online learning and the factors that influence the online learning process. Problem formulation in this study is How effective is e-learning in PKn subjects in grade XI SMAN 1 Tualang and What factors inhibit and encourage the effectiveness of e-learning in PKn subjects in grade XI SMAN 1 Tualang. This study aims to find out the effectiveness of e-learning and the inhibitory factors and drivers of the effectiveness of e-learning in PKn subjects in grade XI SMAN 1 Tualang. The benefits of this research are to be used as a reference for schools and subject teachers in improving the effectiveness of online learning and minimizing the inhibition factors of e-learning. This research was conducted in July-October 2020. The samples in this study were 79 students of SMAN 1 Tualang with Proportional Random Sampling techniques and using the Slovin formula. Researchers used questionnaires, interviews and documentation to gather the data needed to measure the effectiveness of e-learning. Researchers use descriptive-quantitative methods to analyze the data that has been collected. The results of this study showed that e-learning in SMAN 1 Tualang was effective, indicated by the overall score of 6,462 (63.10%) expected score of 10,240 (100%). Most respondents answered the inhibition factor of e-learning is internet quota and unstable network. While the driving factor of e-learning is the desire of students to continue studying even though it is not possible to study in school.Key Words: Effectiveness, Online Learning